ANALISA DAMPAK BENCANA ALAM PADA HUTAN DENGAN ALGORITMA C5.0 STUDI KASUS DINAS KEHUTANAN PROVINSI SUMATERA UTARA - Deviana Christiani Simanjutak (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
The North Sumatra Provincial Forestry Service is a regional apparatus that carries out provincial and district / city regional government affairs in the forestry sector. In the North Sumatra Provincial Forestry Service there were natural disasters. Natural disasters are events or series of events that threaten and disrupt people's lives and livelihoods caused, both by natural and / or non-natural factors as well as human factors, resulting in human casualties, environmental damage, property losses, and psychological impacts. In natural disasters in forests, it is difficult to identify data in determining the magnitude or impact of natural disasters on forests. Handling the impact of natural disasters can be done with the concept of data mining to produce information large or small the impact of existing natural disasters and to help decision making. To produce a decision, the C5.0 algorithm is used, the C5.0 algorithm is an algorithm to make it easier to determine the impact of natural disasters on forests in the North Sumatra Province Forestry.Keywords: Forestry Service, Data Mining, Algoritma C5.0